Gold(I)-catalyzed hydroaminaloxylation and petasis-ferrier rearrangement cascade of aminaloalkynes - Gade, Amol B.; Patil, Nitin T. (Organic Letters, 2016)
An efficient method has been developed to generate a diverse array of indolizidines and quinolizidines from readily available aminaloalkynes via a gold(I)-catalyzed hydroaminaloxylation and Petasis-Ferrier rearrangement cascade. The method enabled a formal synthesis of (+/-)-antofine.

Gold(I)-catalyzed hydroxy group assisted C(sp(2))-H alkylation of enaminones with diazo compounds to access 3-alkyl chromones - Bagle, Pradip N.; Mane, Manoj V.; Sancheti, Shashank P.; Gade, Amol B.; Shaikh, Samir R.; Baik, Mu-Hyun; Patil, Nitin T. (Organic Letters, 2019)
A strategy for expedient synthesis of 3-substituted chromones from easily available o-hydroxyarylenaminones and diazo compounds has been developed. Carefully conducted experimental and computational studies led us to propose an uncommon mechanistic pathway involving the hydroxyl group assisted alkylation of enaminones with in situ generated gold carbenes.